Characteristics and mortality of patients with and without cardio-renal syndrome treated by peritoneal dialysis in France - Gabrielle Duneau; Mabel Aoun (RDPLF, 2022)
Summary Introduction Overall, peritoneal dialysis (PD) is increasingly indicated for refractory heart failure. The aim of this study was to analyze the characteristics and survival of PD patients with and without cardiorenal syndrome (CRS) in France. Methods This was a retrospective study that included all patients enrolled in the French Language Peritoneal Dialysis Registry (RDPLF) between 01/01/2010 and 01/12/2021. The cohort was divided into two groups to compare patients with and without CRS. Survival was analyzed by the Kaplan-Meier method, and the log-rank test was used to compare the two groups. Factors associated with mortality in both groups were identified with Cox regression analysis. Results 11,730 PD patients were included. Their mean age was 66.78±16.72 years. Of these patients, 766 (6.53%) were managed in PD for CRS and 10,964 for another initial kidney disease. Patients with CRS were older and had more comorbidities. Survival was significantly better in the group without CRS. The median survival times were 17.7±1.2 months and 49.6±0.7 months in patients with and without CRS, respectively. Multivariate Cox regression analysis revealed that age, male sex, diabetes, cardiovascular pathology, and lack of autonomy were factors associated with increased mortality in the group without CRS. In patients with CRS, only the variables age and history of liver disease were significantly associated with an increased risk of death. The number of peritonitis episodes with which a patient presented was significantly associated with a lower risk of death in both groups. Conclusion This nationwide study of a large number of patients treated with PD revealed the large differences in characteristics and survival between those with and without CRS. In particular, the two factors most related to mortality in the group with CRS were age and liver disease.